2019
DOI: 10.12804/revistas.urosario.edu.co/apl/a.7175
|View full text |Cite
|
Sign up to set email alerts
|

Polyculturalism: Viewing Cultures as Dynamically Connected and its Implications for Intercultural Attitudes in Colombia

Abstract: En un mundo cada vez más globalizado, estamos cada vez más expuestos a personas y culturas diversas. De ahí la importancia de investigar los sistemas de creencias existentes sobre las influencias transculturales y sus consecuencias. El aumento reciente de la migración hace de Colombia un lugar particularmente interesante para el estudio de las actitudes e intenciones hacia individuos de otras culturas. Hallazgos previos en las Filipinas y Estados Unidos sugieren que la creencia en el policulturalismo —en que l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Compare this to Hong Kong and Macau, where public discourses still make references to the British and Portuguese administrative years, which ended about 20 years prior to the date of the study. But even if the presence of British in Malaysia is not seen as a post-colonial phenomenon, one would still expect that polyculturalism would be positively associated with attitudes toward the British, as previous studies show that polyculturalism is positively associated with attitudes toward foreign nationals (Bernardo et al, 2013; Rosenthal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compare this to Hong Kong and Macau, where public discourses still make references to the British and Portuguese administrative years, which ended about 20 years prior to the date of the study. But even if the presence of British in Malaysia is not seen as a post-colonial phenomenon, one would still expect that polyculturalism would be positively associated with attitudes toward the British, as previous studies show that polyculturalism is positively associated with attitudes toward foreign nationals (Bernardo et al, 2013; Rosenthal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Pertaining to within-society intercultural contact, research on ethnically diverse communities in the United States has shown that belief in polyculturalism is associated with stronger interest in and appreciation of diversity, and with comfort with cultural differences (Rosenthal and Levy, 2010, 2012), with willingness for intergroup contact and friendship intentions with people from different ethnic groups (Rosenthal and Levy, 2016), and positive behavioral intentions and policy attitudes related to Muslim Americans (Rosenthal et al, 2015). Pertaining to between-society intercultural contact, polyculturalism is also associated with more positive attitudes and friendship intentions toward people from foreign countries (Bernardo et al, 2013), toward migrant groups (Rosenthal et al, 2019), less prejudice toward refugees (Healy et al, 2017), and cognitive empathy for actors in intercultural situations (Salanga and Bernardo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Polikulturalisme dianggap menumbuhkan sikap dan perilaku antar kelompok gender, etnis, dan agama yang lebih positif dengan meminimalisasi batasan budaya di satu sisi, sementara pada sisi lain menekankan persamaan dalam hubungan di antara anggota kelompok yang berbeda, sembari tetap mengakui pentingnya identitas asal . Dalam beberapa penelitian terdahulu dijelaskan bahwa terdapat empat komponen dari polyculturalism, yaitu adanya kemauan untuk kontak antar kelompok dan inter-group attitudes yang positif terhadap individu dari kelompok minoritas atau sub-ordinate, serta kelompok migran (Bernardo et al, 2013;Rosenthal et al, 2015Rosenthal et al, , 2019, prasangka antar kelompok yang lebih rendah (Healy et al, 2017), kemampuan untuk bersikap evaluatif dan berfungsi secara efektif dalam lingkungan yang beragam (Bernardo & Presbitero, 2017), sikap positif terhadap akomodasi dan percampuran budaya (Cho et al, 2017).…”
Section: Pendahuluanunclassified
“…There is also a theoretical basis for a positive association between CQ and polyculturalism, as numerous studies have documented the positive relationship between polyculturalism and intercultural attitudes or behavioral intentions. For example, endorsement of polyculturalism is positively associated with interest in and appreciation of diversity (Rosenthal & Levy, 2010;2012), willingness to engage in intergroup contact and build friendships with people from other cultural or ethnic groups (Rosenthal, Levy, London, & Lewis, 2016) or other countries (Bernardo, Rosenthal, & Levy, 2013;Rosenthal, Ramirez, Levy, & Bernardo, 2019), and less negative attitudes toward cultural minorities and refugees (Healy, Thomas, & Pedersen, 2017;Rosenthal, Levy, Katser, & Bazile, 2015). More pertinent to the December 2019 ½Vol.…”
Section: Introductionmentioning
confidence: 99%